PERANCANGAN TURBIN PELTON SEBAGAI PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO DI SUNGAI JLAMPRANG DESA GENITO, WINDUSARI - Yanuar Nugraha Husni Maulana Yanuar (ELEMEN : JURNAL TEKNIK MESIN, 2025)
This study discusses the design of a Pelton turbine for a Micro Hydro Power Plant (PLTMH) in the Jlamprang River, Genito Village, Windusari. The goal is to utilize the potential of river flow with a large head and water discharge as a source of renewable energy. The methods include power potential analysis, turbine design using CAD, and dynamic fluid simulation with ANSYS to evaluate performance. Design optimization is carried out by considering various jet velocities, namely 45 m/s, 50 m/s, and 55 m/s. The optimal jet speed of 55 m/s produces 53 kW of power, 86% efficiency, 1124 Nm of torque, and 8.2 Pa of pressure, although turbulence increases. The design involves adjusting the nozzle diameter, number, and dimensions of the blades to maximize performance. The results show optimal fluid distribution, making this PLTMH a sustainable energy solution for rural areas. This technology is expected to increase the energy independence of Genito Village and reduce dependence on conventional electricity.